Influence of non-uniform martensitic transformation on residual stresses and distortion of GMA-welding. (January 2017) - Neubert, S.; Pittner, A.; Rethmeier, M.
Abstract: A combined experimental and numerical approach is applied for a numerical analysis of the non-uniform martensitic transformation kinetic on welding residual stresses and distortion of a single pass weld. The (γ → α)-transformation kinetic within the weld pool region is governed by a non-uniform distribution of the elements chromium and nickel. The single-pass weld was performed by use of the low-alloyed high-strength steel S960QL with the high-alloyed high-strength filler wire CN 13/4-IG®. A thermo-mechanical FE model of the welding process was experimentally validated against temperature field, solid phase distribution, transformation behaviour, X-Ray stress measurements and transient optical distortion measurements. The experimentally determined and calculated weld residual stresses and transient distortion are in good agreement. It can be shown that the change on the (γ → α)-transformation kinetic driven by the inhomogeneous distribution of the chemical contents causes a strong influence on the weld residual stresses within the volume of the weld pool, which could promote crack propagation within the solidified weld pool by use of high-alloyed filler materials. Furthermore, a significant influence on the development of the transient welding distortion is visible. This influence should be respected during numerically calculation of welding distortion in case of multi-pass welding using interpass temperatures and high-alloyed filler materials. Highlights: Use of an experimentally validated numerical model which describes a single pass dissimilar weld joint. Use of wavelength dispersive X-Ray spectroscopy to analyze Cr-Ni-distribution within the region of the solidified weld pool Experimental and calculated welding residual stresses and distortion show good agreement. Impact of non-uniform Cr-Ni-distribution in the weld pool region on residual stresses and transient distortion is clarified. Graphical abstract: